Comparison of lactation curve models for fortnightly test day milk yield - ARYA, VINEETA; SHAHI, B N; KUMAR, D; BARWAL, R S; KUMAR, SUNIL; GAUTAM, LOKESH (The Indian Journal of Animal Sciences, 2020)
The study of lactation curve helps to predict lactation milk production at a certain point of time and provides useful information for taking desirable decisions on preliminary sire evaluation, early culling of poor producers, breeding and feeding management and comparison of lactation records of unequal length. The test day milk yield data on 511 crossbred cattle were obtained and utilized according to fortnightly interval upto 305th day maintained at Instructional Dairy Farm, G B Pant University of Agriculture and Technology, Pantnagar (Uttarakhand). The different statistical models predicting the shape of lactation curve considered were exponential function, parabolic exponential function, inverse polynomial function and gamma type function. For fortnightly test day milk yield, the inverse polynomial function exhibited the highest coefficient of determination (R2=99.97%) followed by parabolic exponential (89.32%), gamma type (87.26%) and exponential function (35.70). Inverse polynomial function is the best fitted function for explaining the first lactation curve by utilizing the records of fortnightly test day milk yields.